STUDI NUMERIK RESPON STRUKTUR MODIFIKASI BANTALAN BETON UNTUK NON-BALLASTED TRACK - Danang Purwanto; Iman Satyarno; Andreas Triwiyono (TEKNISIA, 2019)
According to Rencana Induk Perkeretaapian Nasional (RIPNas), making  plans for the development of Indonesian railways until the next 2030. The targets for the development of railway networks and services to be achieved in 2030 include a national network of 12,100 km (spread on Java-Bali, Sumatra, Kalimantan, Sulawesi and Papua). Construction of railway track is generally divided into two main types, namely, ballasted tracks and non-ballast tracks.  In this study the non-ballasted track or ballastless track is to modify the width of the sleeper  that will be used without using ballasts on the railroad tracks. This is done to reduce the use of coarse aggregates in ballasts so that if used in areas that do not have natural resources in the form of coarse aggregates a railway track can be built. The research will be carried out according to the condition of the soil gravel, dense sand, medium dense sand, silty medium dense dan loose sand. Different types of soil cause different responses or behaviors from the modification of the sleeper  that are located above the ground. This study will discuss the analysis of rail displacement and rail bending stress that occur in the modification of railroad concrete sleeper  for non-ballast use in some soil conditions. The study was conducted with software SAP2000 version 2014 to analyze  displacement and rail bending stress on concrete sleeper modification with dimensions 400 x 2440 mm2; 1200 x 2440 mm2; 2000 x 2440 mm2; 2800 x 2440 mm2 dan 3600 x 2440 mm2 for each different type of soil to determine the dimensions of modification of concrete sleeper  that can be used. According AREMA(1999) Result of rail displacement rail may not exceed 6 mm and rail bending  stress may not exceed 75 N/mm2.